LINGUISTIC INTERPRETATION OF THE CONCEPT (World Bulletin of Social Sciences, 2023)
According to scientists, another basis for distinguishing between linguistic and cultural concepts is that they belong to the field of knowledge and consciousness. Of course, "there is no national science, just as there is no national multiplication table", but there are specific lexical units whose "next meaning" is the substantive basis of the moral, psychological meaning, logical and religious terms - "spiritual values", they are undoubtedly it can be determined ethno-culturally both within the boundaries of one language and within the boundaries of an inter-linguistic scientific paradigm - way of thinking
Keywords: linguistic; cultural